Perivascular Adipose Tissue's Impact on Norepinephrine-Induced Contraction of Mesenteric Resistance Arteries - Ayala-Lopez, Nadia; Thompson, Janice M.; Watts, Stephanie W. (Frontiers in Physiology, 2017)
Background: Perivascular adipose tissue (PVAT) can decrease vascular contraction to NE. We tested the hypothesis that metabolism and/or uptake of vasoactive amines by mesenteric PVAT (MPVAT) could affect NE-induced contraction of the mesenteric resistance arteries. Methods: Mesenteric resistance vessels (MRV) and MPVAT from male Sprague-Dawley rats were used. RT-PCR and Western blots were performed to detect amine metabolizing enzymes. The Amplex® Red Assay was used to quantify oxidase activity by detecting the oxidase reaction product H2O2 and the contribution of PVAT on the mesenteric arteries’ contraction to NE was measured by myography. Results: Semicarbazide sensitive amine oxidase (SSAO) and monoamine oxidase A (MAO-A) were present in MRV and MPVAT by Western blot. Addition of the amine oxidase substrates tyramine or benzylamine (1 mM) resulted in higher amine oxidase activity in the MRV, MPVAT, MPVAT’s adipocyte fraction (AF) and the stromal vascular fraction (SVF). Inhibiting SSAO with semicarbazide (1 mM) decreased amine oxidase activity in the MPVAT and AF. Benzylamine-driven, but not tyramine-driven, oxidase activity in the MRV was reduced by semicarbazide. By contrast, no reduction in oxidase activity in all sample types was observed with use of the monoamine oxidase inhibitors clorgyline (1 uM) or pargyline (1 uM). Inhibition of MAO-A/B or SSAO individually did not alter contraction to NE. However, inhibition of both MAO and SSAO increased the potency of NE at mesenteric arteries with PVAT. Addition of MAO and SSAO inhibitors along with the H2O2 scavenger catalase reduced PVAT’s anti-contractile effect to NE. Inhibition of the norepinephrine transporter (NET) with nisoxetine also reduced PVAT’s anti-contractile effect to NE.